The impact of technology absorption capacity on competitive advantage in Vietnamese small and medium enterprises - Thuy, Nguyen Van (Edelweiss Applied Science and Technology, 2024)
This study examines the impact of technology absorption capacity on competitive advantage in Vietnamese small and medium enterprises. Technology absorptive capacity can help SMEs enhance their competitive advantage by improving customer interactions, optimizing business processes, encouraging innovation, expanding markets, and increasing transparency and trustworthiness. The study assessed the impact of technology absorptive capacity on SME’s competitive advantage. The research team conducted a questionnaire survey to assess the impact of technology absorption capacity on the competitive advantages of 300 Vietnamese small and medium-sized enterprises, specifically those engaged in digital transformation and the integration of technologies into their production and business activities. With the survey data collected, the study uses quantitative analysis methods, including steps to evaluate the reliability of variables in the model based on the Cronbach Alpha coefficient; Exploratory Factor Analysis (EFA) and Confirm Factor Analysis (CFA) are used to identify and confirm the factors and scales in the model, Structural Equation Modeling (SEM) is applied to determine the impact relationship between the factors and variables in the research model. The results show that technology absorption capacity has a strong impact on the innovation business model, strategic flexibility, and competitive advantage of the SME. Based on the results, the study has given some specific policy implications for the digital transformation process to enhance technological capacity through identifying and applying emerging technologies to current small and medium enterprises.